Katherine Mansfield in the World of Modernist Magazines - Kascakova, Janka (Hungarian Journal of English and American Studies, 2020)
Book review: Mourant, Chris. Katherine Mansfield and Periodical Culture. Edinburgh: Edinburgh UP, 2019. 301 pages. ISBN 9781474439459. Hb. £80.